Comparative Studies with tox(+) and tox(−) Corynebacteriophages - Holmes, Randall K. (1970)
The characteristics of nine inducible temperate corynebacteriophages designated α(tox+), β(tox+), P(tox+), γ(tox−), π(tox+), K(tox−), ρ(tox−), L(tox+), and δ(tox+) have been compared. Virion morphology and ability to recombine genetically with the well-studied phage β(tox+) have been correlated with other properties of the phages, and the distribution of the genetic marker tox+ among related and relatively unrelated corynebacteriophages has been analyzed. The immunity specificity, host range, and plaque morphology of each phage were determined. The phages can be separated into five groups with different immunity specificities. Each type of host range previously recognized in mutants of phage β(tox+) was present in one or more of the phages included in the present study, and the phages were found to produce plaques of several different morphological types. Representative phages with each of the five types of immunity specificity were further characterized with respect to virion morphology, ability to recombine with phage β(tox+), latent period, average burst size, and neutralization by homologous and heterologous antiphage sera. All of these phages have polyhedral heads and long slender tails, but two distinct morphological types were distinguished by the sizes and proportions of the components of the virions. Only phages of the same morphological type as β(tox+) were capable of genetic recombination with β(tox+), but morphological similarity between phages was not sufficient to insure interfertility. The phages which recombined with β(tox+) resembled one another in plaque morphology, latent period, and average burst size, whereas phages which failed to recombine with β(tox+) differed in these characteristics. The phages capable of genetic recombination with β(tox+) were found to differ from each other in immunity specificity, host range, neutralization by antiphage sera, and toxinogenicity. Thus, these latter characteristics are of limited value in establishing the extent of relatedness between corynebacteriophages. The genetic marker tox+ was not consistently correlated with any other property of the corynebacteriophages analyzed in this study. The most striking finding regarding the distribution of the tox+ marker is its presence both in β(tox+) and δ(tox+), phages which fail to recombine genetically and which differ in virion morphology. The presence of the tox+ marker in genetically unrelated corynebacteriophages poses many questions concerning the origin(s) of tox+ and the evolution of the phage-host interactions which determine the ability of corynebacteria to synthesize diphtherial toxin.